2024
DOI: 10.1038/s41598-024-54771-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed miRNAs associated with diamide detoxification pathways in Spodoptera frugiperda

Rashmi Manohar Mahalle,
Weilin Sun,
Omar A. Posos-Parra
et al.

Abstract: The fall armyworm (FAW) Spodoptera frugiperda is a severe economic pest of multiple crops globally. Control of this pest is often achieved using insecticides; however, over time, S. frugiperda has developed resistance to new mode of action compounds, including diamides. Previous studies have indicated diamide resistance is a complex developmental process involving multiple detoxification genes. Still, the mechanism underlying the possible involvement of microRNAs in post-transcriptional regulation of resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
0
0
Order By: Relevance
“…Many studies have reported the involvement of ABC transporters in chlorantraniliprole and flubendiamide detoxification in other species such as Chilo suppressalis (Walker) (Lepidoptera: Crambidae) [53], P. xylostella [54], S. frugiperda [55] and Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae) [44]. The Multidrug resistance-associated protein 1 (MDR1), also known as P-glycoprotein (P-gp), is encoded by ATP-binding cassette subfamily B member 1 (ABCB1) [56,57].…”
Section: On the Other Hand The Voltage-dependent T-type Calcium Chann...mentioning
confidence: 99%
“…Many studies have reported the involvement of ABC transporters in chlorantraniliprole and flubendiamide detoxification in other species such as Chilo suppressalis (Walker) (Lepidoptera: Crambidae) [53], P. xylostella [54], S. frugiperda [55] and Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae) [44]. The Multidrug resistance-associated protein 1 (MDR1), also known as P-glycoprotein (P-gp), is encoded by ATP-binding cassette subfamily B member 1 (ABCB1) [56,57].…”
Section: On the Other Hand The Voltage-dependent T-type Calcium Chann...mentioning
confidence: 99%